Indonesia Sovereign Wealth Fund and Accountability State Wealth Management: The Relevance of External Audit by the Office Public Accountant or Constitutional Audit by the State-Audit Board - Tanjung, Afriansyah; Thahira, Agniya; Ummah, Maela Khoirul (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This study explores the accountability framework of Indonesia’s Sovereign Wealth Fund (SWF), known as the Lembaga Pengelola Investasi (LPI) or Indonesia Investment Authority (INA), focusing on the legal and institutional mechanisms that ensure its transparent and professional operation. Design/methodology/approach – The research addresses concerns over the management of public wealth derived from the state budget and other state assets, emphasizing the relevance of dual oversight by the Audit Board of Indonesia (BPK) and Public Accounting Firms (KAP). Using a qualitative, library-based research methodology with conceptual and statute-based approaches, the study draws on legal statutes, academic literature, and international case studies—particularly Norway’s GPFG and Singapore’s Temasek Holdings. Findings – The Findings highlight that dual-audit mechanisms are both constitutionally mandated and functionally complementary: BPK ensures public accountability and legal compliance, while KAP provides internationally credible financial assurance to investors. Originality – The study identifies governance risks drawn from past corruption in State-Owned Enterprises (BUMN) and proposes a dual-audit framework as a safeguard against similar failures. It contributes to the legal and public finance discourse by providing a normative and empirical justification for multi-layered oversight in managing Indonesia’s strategic public investments. Keywords: INA, BPK, Public Accounting Firms, Dual-Audit Mechanism. Paper Type Research Result